Answer:
i dk but i will try
C
Step-by-step explanation:
Answer:
32 n
Step-by-step explanation:
I had the same problem but I used a net force calculator the formula is F=MA so it would be 32=16/2.0 :)
We have the following function:
f (x) = 2a ^ 2b + 3a ^ 3b ^ 2 + 2a ^ 2b ^ 4
We note that the function depends on x because it is f (x).
However, there is no variable x in the function.
Therefore we can assume that the function is constant, since:
a = constant
b = constant
Therefore, the degree of the function is zero
Answer:
The function is zero degree.
Answer:
y=-2x+11
Step-by-step explanation:
equation of a line
y-b=m(x-a)
m=-2
a=3
b=5
sub into the equation
y-5= -2(x-3) multiply out the brackets and a negative multiply by negative equals positive
y-5=-2x+6
y=-2x+11
or
2x+y-11=0
Answer:
£23
Explanation:
6x10=60
2x1.5=3
3.14x2^2=12.566
60-3-12.566=44.433
44.43/10=4.43
5 bags
5x4.60=23
=£23